Rematuration Periods and Sperm Characteristics of Litopenaeus vannamei - Anwar, L. Okmawati; Sumantadinata, K.; Carman, O. (Jurnal Akuakultur Indonesia, 2007)
The reproduction ability of male has an important role in seeds production of Litopenaeus vannamei. The objective of research was to know the sperm characteristics from each rematuration period. The research conducted in Broodstock and Nauply Quality Control Laboratory, Central Pertiwi Bahari, Lampung Province on April until July 2006. Five male shrimps obtained from High Health, Aquaculture Inc., Hawaii-USA, about 39.4 ± 1.51 g in weight and 16.4 ± 0.43 cm in length. Carefull stripping was applied to release the mature spermatophore from the thelicum. The results showed that number of sperm at the first to fourth rematuration period relatively constant (33.62x106 - 39.7402x106 cell). However the number of abnormal sperm were relatively increase slightly (1.2806x106 to 23.3576x106 cell) and also the number of death sperm (0.293x106 to 3.92x106 cell) while the number of normal sperm were relatively decrease (29.1158x106 to 23.3576x106 cell). There were no changes in head size and tail lenght of the sperm from each rematuration periods. Keywords:  Litopenaeus vannamei, spermatozoa, rematuration   ABSTRAK Kemampuan reproduksi udang jantan berperan penting dalam pembenihan udang vaname Litopenaeus vannamei. Penelitian ini bertujuan untuk mengetahui karakteristik sperma pada setiap periode rematurasi. Penelitian dilaksanakan di Laboratorium Kendali Mutu Induk dan Naupli, Central Pertiwi Bahari, Propinsi  Lampung, bulan April sampai Juli 2006. Udang jantan yang digunakan berasal dari High Health, Aquaculture Inc., Hawaii-USA, dengan ukuran berat 39,4 ± 1,51 g, panjang tubuh 16,4 ± 0,43 cm dan berjumlah lima ekor sebagai ulangan. Spermatofor dilepaskan dari telikum dengan teknik  pengurutan. Hasil penelitian menunjukkan jumlah sperma relatif stabil pada empat kali rematurasi (33,62x106 - 39,7402x106 sel). Jumlah sperma abnormal dan sperma mati berbanding terbalik dengan jumlah sperma normal. Jumlah sperma abnormal meningkat dari rematurasi pertama hingga rematurasi ke empat (1,2806x106 ke 23,3576x106 sel) demikian halnya jumlah sperma mati (0,293x106 ke 3,92x106 sel), sedangkan jumlah sperma normal mengalami penurunan (29,1158x106 ke 23,3576x106 sel). Tidak terdapat perubahan ukuran kepala dan panjang ekor sperma dalam setiap periode rematurasi. Kata kunci :  Litopenaeus vannamei, spermatozoa, rematurasi